Complex Bronchofibroscopy in the Diagnosis of Pulmonary Complications in Intensive Care Unit Patients - G. E. Roitberg; V. D. Kreimer; I. V Smirnov; O. B., Malova; N. E. Larina; S. A. Tarabarin; I. A. Khomyakova (Общая реаниматология)
Objective: to determine the efficiency of bronchofibroscopy (BFS) and cytology of bronchoalveolar lavage fluid (BALF) for the diagnosis of pulmonary complications in resuscitation patients with varying acute therapeutic and surgical diseases. Subjects and methods. Twenty-seven patients treated at the intensive care unit of the Meditsina Clinic (the clinical basis of the Department of Therapy and Family Medicine, N. I. Pirogov Russian National Research Medical University) were examined. Sanitation BFSs were performed, by taking BALF for cytological examination. Results. BALF hyperneutrophil-ia is characteristic of the patients who are critically ill (an APPACHE-II score of more than 21). All the patients were diagnosed as having Grades 1 and 2 inflammatory changes in the airway mucosa. Conclusion. The introduction of cytological examination of BALF into the practice of intensive care units of multidisciplinary health care facilities considerably increases the quality and efficiency of resuscitative measures and promotes shorter treatment duration. Key words: bronchofi-broscopy, pulmonary complications, diagnosis, bronchoalveolar lavage fluid, cytology.